The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2020.598721
|View full text |Cite
|
Sign up to set email alerts
|

Deep CNN Model Using CT Radiomics Feature Mapping Recognizes EGFR Gene Mutation Status of Lung Adenocarcinoma

Abstract: To recognize the epidermal growth factor receptor (EGFR) gene mutation status in lung adenocarcinoma (LADC) has become a prerequisite of deciding whether EGFR-tyrosine kinase inhibitor (EGFR-TKI) medicine can be used. Polymerase chain reaction assay or gene sequencing is for measuring EGFR status, however, the tissue samples by surgery or biopsy are required. We propose to develop deep learning models to recognize EGFR status by using radiomics features extracted from non-invasive CT images. Preoperative CT im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 49 publications
(61 reference statements)
0
30
0
Order By: Relevance
“…By analyzing ROC curves, calibration curves and decision curves, we found that our novel radiomic models not only had high accuracy and robustness, but they also had high clinical gain. As shown in Table S5, several former studies (32,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) also tried to build radiomics-based classifiers to predict EGFR mutation or Ki-67 PI expression in lung cancer.…”
Section: Model Performancementioning
confidence: 99%
“…By analyzing ROC curves, calibration curves and decision curves, we found that our novel radiomic models not only had high accuracy and robustness, but they also had high clinical gain. As shown in Table S5, several former studies (32,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) also tried to build radiomics-based classifiers to predict EGFR mutation or Ki-67 PI expression in lung cancer.…”
Section: Model Performancementioning
confidence: 99%
“…The results of this study confirmed the reliability of radiomic and deep learning models for the non-invasive prediction of EGFR mutation status in lung adenocarcinoma with a high degree of accuracy. In lung adenocarcinoma patients, two previous studies (39,40)combined both radiomic and clinical features to successfully build a radiomic-clinical model that could efficiently identify EGFR mutant phenotypes from wild types with good AUCs of 0.779 and 0.823. However, two other studies (41,42) also successfully built a combined radiomic-clinical prediction model but also found that a deep learning feature-based model could also predict EGFR gene mutation status in patients with lung adenocarcinoma in a more accurate manner, achieving AUCs of 0.810 and 0.758.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of precision medicine, there is a trend that patients with lung cancer are treated only after having their gene expression clarified. Some previous studies have used deep learning technology to predict EGFR, PD-L1, or ALK gene status, respectively, and achieved favorable performances (Table 3) [18,19,[29][30][31][32][33][34]. However, these previous studies focused specifically on predicting mutation status in only one gene.…”
Section: Discussionmentioning
confidence: 99%